PENGARUH KEPEMIMPINAN TERHADAP KINERJAKARYAWAN CV. ZANAFA PEKANBARU - Dehotman, Khornelis (Sekolah Tinggi Ilmu Ekonomi Riau, 2020)
The purpose of this study was to determine how much influence leadership has on the performance of employees CV. Zanafa Pekanbaru. The population in this study were employees at CV. Zanafa Pekanbaru numbered 31 employees. To determine the number of samples, research use the theory in Sugionoâ€™s book (2017:146), namely research conducted on populations below 100 should be carried out by census (total sampling) so that the entire populations is sampled. Data analysisnused was validity, realibility, simpleÂ linier regression and the t test. The test is to find out the relationship between the independent variable and dependent variable. The final conclusin of this study id the correlation coefficient (r2) obtained 0,252 wich show relationship between leadership influence with employee performance CV. Zanafa Pekanbaru. while the persentage of leadership influence on employee performance CV. Zanafa Pekanbaru by 25,2% with the resultÂ of the hypothesis test t count : 3,068 > t tabel 2,04. Then Ha is accepted and H0 is rejected, wich means there is asignificant relationship between leadership and employee performance CV. Zanafa Pekanbaru. While the result of a simple linier regression equation is Y = 19,596 +0,15 X